2013
DOI: 10.1186/1471-2458-13-464
|View full text |Cite
|
Sign up to set email alerts
|

Methods to increase participation in organised screening programs: a systematic review

Abstract: BackgroundThe European Community recommends the implementation of population-based screening programmes for cervical, breast, and colorectal cancers. This recommendation is supported by many observational studies showing that organised programmes effectively reduce mortality and control the inappropriate use of screening tests. We conducted a systematic review of studies assessing the efficacy of interventions to increase participation in organised population-based screening programs.MethodsWe included all stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
171
2
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(186 citation statements)
references
References 92 publications
(142 reference statements)
5
171
2
6
Order By: Relevance
“…Patient reminders have been shown to be effective in increasing breast and cervical cancer screening rates. [29][30][31][32] Reported NCQA recognition as a PCMH also was associated with increased use of comparative performance reports and automated reports to alert providers of patients due for cancer screening outside the context of the clinical visit. Theoretical and empirical evidence supports the efficacy of physician audits and feedback in improving cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Patient reminders have been shown to be effective in increasing breast and cervical cancer screening rates. [29][30][31][32] Reported NCQA recognition as a PCMH also was associated with increased use of comparative performance reports and automated reports to alert providers of patients due for cancer screening outside the context of the clinical visit. Theoretical and empirical evidence supports the efficacy of physician audits and feedback in improving cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…This simple, affordable intervention is acceptable to many and similar print interventions have increased uptake of cancer screening. 35 Given that some participants cited lack of GP advice on screening as a reason for not wanting screening advice, general practitioner endorsement may increase the acceptability of receiving screening advice.…”
Section: Implications For Public Healthmentioning
confidence: 99%
“…Camilloni et al 32 recently updated the landmark review by Jepson et al, 33 focusing on methods to increase uptake of screening for breast, cervical or colorectal cancer. The review suggested that postal reminders in addition to the initial invitation could significantly increase uptake, whereas the evidence for telephone reminders was largely favourable, although some primary studies did not demonstrate significant effects.…”
mentioning
confidence: 99%
“…32 Kumar et al 35 compared health check uptake by patients offered only a booked appointment with uptake by patients offered a choice of a booked appointment or attending a drop-in clinic. Uptake rates for the two groups separately are not reported, but the authors suggested that use of drop-in clinics may be less costly.…”
mentioning
confidence: 99%
See 1 more Smart Citation